(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
According to experts’ estimates, 30-40 thousand children with congenital CMV infection are born each year in the USA alone, i.e. it is far ahead of all other congenital infections in terms of frequency and significance. The nature of fetal damage, as in other infectious diseases, depends on the timing of infection [3,4,5].